2017
DOI: 10.1111/cas.13388
|View full text |Cite
|
Sign up to set email alerts
|

Tumor endothelial cells with high aldehyde dehydrogenase activity show drug resistance

Abstract: Tumor blood vessels play an important role in tumor progression and metastasis. We previously reported that tumor endothelial cells (TEC) exhibit several altered phenotypes compared with normal endothelial cells (NEC). For example, TEC have chromosomal abnormalities and are resistant to several anticancer drugs. Furthermore, TEC contain stem cell‐like populations with high aldehyde dehydrogenase (ALDH) activity (ALDH high TEC). ALDH high TEC have proangiogenic properties compared with ALDH low TEC. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
(72 reference statements)
1
39
1
Order By: Relevance
“…TECs are not only involved in the angiogenesis process to support primary tumor growth, but also promote tumor progression, metastasis and drug resistance [41]. TECs contain stem cell-like populations and overexpress MDR1 and aldehyde dehydrogenase (ALDH) and become resistant to chemotherapeutics such as paclitaxel and 5-fluorouracil in vitro [43,44].…”
Section: Tumor Endothelial Cells (Tecs)mentioning
confidence: 99%
“…TECs are not only involved in the angiogenesis process to support primary tumor growth, but also promote tumor progression, metastasis and drug resistance [41]. TECs contain stem cell-like populations and overexpress MDR1 and aldehyde dehydrogenase (ALDH) and become resistant to chemotherapeutics such as paclitaxel and 5-fluorouracil in vitro [43,44].…”
Section: Tumor Endothelial Cells (Tecs)mentioning
confidence: 99%
“…A new study showed that targeted elimination of macrophages elicited a type I interferon response in the tumor milieu that enhances the efficacy of platinum, but not taxane-based chemotherapy, underlining complicated regulatory roles for macrophages in chemotherapy-treated tumors [67]. TECs with high aldehyde dehydrogenase activity showed drug resistance [68]. TECs and TAMs can play key roles in drug resistance inasmuch as these tumorassociated cells often express drug resistance genes [69][70][71][72][73][74].…”
Section: Stromal Signal-driven Tumor Progressionmentioning
confidence: 99%
“…High ALDH1 activity is also an in vitro and in vivo hallmark of CSCs. Patients with tumor cells with high ALDH1 levels often exhibit therapeutic resistance and have a poor prognosis [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%